2012
DOI: 10.1002/btpr.1554
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐scale bioprocessing systems for highly parallel animal cell cultures

Abstract: Animal cells have been used extensively in therapeutic protein production. The growth of animal cells and the expression of therapeutic proteins are highly dependent on the culturing environments. A large number of experimental permutations need to be explored to identify the optimal culturing conditions. Miniaturized bioreactors are well suited for such tasks as they offer high-throughput parallel operation and reduce cost of reagents. They can also be automated and be coupled to downstream analytical units f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…The 12 cell lines were then assessed in shake tubes, microscale, and lab‐scale bioreactors under similar conditions to verify the maintenance of the performance obtained in the 96‐DWP model across scales. Indeed, cell line behavior might be different in vessels like 96‐DWP, shake tubes, and shake flasks which do not control critical parameters such as pH, DO, and p CO 2 , when compared with bioreactors which control these parameters online . On the other hand, several studies showed that microscale bioreactors can be used as reliable scale‐down models of conventional stirred bioreactors, giving similar process performance profiles and quality data .…”
Section: Discussionmentioning
confidence: 99%
“…The 12 cell lines were then assessed in shake tubes, microscale, and lab‐scale bioreactors under similar conditions to verify the maintenance of the performance obtained in the 96‐DWP model across scales. Indeed, cell line behavior might be different in vessels like 96‐DWP, shake tubes, and shake flasks which do not control critical parameters such as pH, DO, and p CO 2 , when compared with bioreactors which control these parameters online . On the other hand, several studies showed that microscale bioreactors can be used as reliable scale‐down models of conventional stirred bioreactors, giving similar process performance profiles and quality data .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, microbioreactors have transformed early-stage process development by providing controlled culture environments at a high degree of parallelization and short turnover times [1][2][3][4][5]. Applikon's (The Netherlands) micro-Matrix is a platform that holds 24 microbioreactors on a deep-square well format and offers full control of pH and dissolved oxygen in each well [6].…”
Section: Methods Summarymentioning
confidence: 99%
“…The number of live and dead cells present in the whole culture is finally obtained by multiplying the number of counted cells by the dilution factor used. Despite its simplicity, several problems affect the manual counting procedure [55]. First of all, these counts are performed manually and are thus they are labour intensive [56] and operator dependent [57].…”
Section: Cell Counting Approachesmentioning
confidence: 99%